Lignans - Barker, David (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Lignans are a class of natural products found mainly in plants. They have a wide variety of structures and exhibit a range of potent biological activities. Lignans are also well-known components of a number of widely eaten foods and are frequently studied for their dietary impact. Owing to these factors, lignans have been extensively studied by scientists from a large number of disciplines. This collection of research and review articles describes topics ranging in scope from the recent isolation and structural elucidation of new lignans, strategies towards the chemical synthesis of lignans, assessment of their biological activities and potential for further therapeutic development. Research showing the impact of lignans in the food and agricultural industries is also presented.